ANALISIS KAUSALITAS DAN KOINTEGRASI ANTARA PERBANKAN SYARIAH DAN PERTUMBUHAN EKONOMI JAWA TIMUR - H, Amalia Nuril; Cholifah, Siti Nur; Rohman MZ, Muhammad Abd (IAIN Tulungagung, 2019)
This study aims to examine the causal relationship between Islamic banking and East Java's economic growth and the long-term relationship (cointegration) between Islamic banking and East Java economic growth for the period 2010-2017. The variables used in this study are total financing and total third party funds of Islamic banking as a representation of Islamic banking. While economic growth is represented by East Java Gross Regional Domestic Product (GRDP). Data analysis using Granger Causality Test and Johansen Cointegration Test with the help of software Eviews 9. The results showed that there is a two-way causality relationship between Islamic banking and East Java economic growth. Islamic banking influences the economic growth of East Java, and conversely economic growth influences Islamic banking. In addition, there is a long-term relationship (cointegration) between Islamic banking and economic growth in East Java. The rapid development of Islamic banking will provide benefits for economic growth and this will have a long-term impact on the welfare and well-being of the people in East Java